2018
DOI: 10.2147/ott.s175112
|View full text |Cite
|
Sign up to set email alerts
|

Elevated urinary 8-oxo-7,8-dihydro-2'-deoxyguanosine and serum uric acid are associated with progression and are prognostic factors of colorectal cancer

Abstract: Background and purposeOxidative stress is closely related to the pathogenesis of colorectal cancer (CRC). 8-Oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) is a typical bio-marker of oxidative stress. Serum uric acid (SUA) is one of the most abundant molecules with antioxidant properties in human blood. This study aimed to explore whether 8-oxodG and SUA could be prognostic factors of CRC.MethodsUrinary 8-oxodG level was analyzed using ultrahigh performance liquid chromatography-tandem mass spectrometry (UPLC-MS/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(34 reference statements)
0
10
0
Order By: Relevance
“… Healthy controls Patients Methods Ref. ‘DNA’ oxidation 3.68 (n = 61) 4.58 (n = 57; unipolar and bipolar disorders) LC-MS/MS [ 308 ] 8-oxodG (ng/mg creatinine) 2.53 (n = 70) 3.46 (n = 148; bipolar I disorder) UPLC-MS/MS [ 309 ] 3.90 (n = 128) 4.35 (n = 87; COPD); 14.6 (n = 100; patients with mechanical ventilation) LC-MS/MS [ 241 ] 4.13 (n = 16) 5.23 (n = 46; renal disease) LC-MS/MS [ 310 ] 2.80 (n = 73) 4.71 (n = 60; breast cancer) UPLC-MS/MS [ 311 ] - a 5.41 (n = 12; colorectal cancer) UPLC-MS/MS [ 312 ] 6.76 (n = 508; cardiovascular disease) UPLC-MS/MS [ 313 ] 4.62 (n = 2721; type 2 diabetes) UPLC-MS/MS [ 314 ] 5.27 (n = 609; type 2 diabetes) UPLC-MS/MS [ 109 ] 2.03 (n = 60) UPLC-MS/MS [ 315 ] 7.83 (n = 132) …”
Section: Nucleic Acid Oxidation In Human Health and Diseasementioning
confidence: 99%
“… Healthy controls Patients Methods Ref. ‘DNA’ oxidation 3.68 (n = 61) 4.58 (n = 57; unipolar and bipolar disorders) LC-MS/MS [ 308 ] 8-oxodG (ng/mg creatinine) 2.53 (n = 70) 3.46 (n = 148; bipolar I disorder) UPLC-MS/MS [ 309 ] 3.90 (n = 128) 4.35 (n = 87; COPD); 14.6 (n = 100; patients with mechanical ventilation) LC-MS/MS [ 241 ] 4.13 (n = 16) 5.23 (n = 46; renal disease) LC-MS/MS [ 310 ] 2.80 (n = 73) 4.71 (n = 60; breast cancer) UPLC-MS/MS [ 311 ] - a 5.41 (n = 12; colorectal cancer) UPLC-MS/MS [ 312 ] 6.76 (n = 508; cardiovascular disease) UPLC-MS/MS [ 313 ] 4.62 (n = 2721; type 2 diabetes) UPLC-MS/MS [ 314 ] 5.27 (n = 609; type 2 diabetes) UPLC-MS/MS [ 109 ] 2.03 (n = 60) UPLC-MS/MS [ 315 ] 7.83 (n = 132) …”
Section: Nucleic Acid Oxidation In Human Health and Diseasementioning
confidence: 99%
“…Evidence has shown that preoperative SUA is an independent prognostic predictor in esophageal squamous cell carcinoma patients who undergo R0 esophagectomy, and patients with a higher SUA level might have significantly shorter 1, 3, and 5 year survival times than patients with a relatively low SUA level [22]. For colorectal cancer (CRC), it was found that SUA levels gradually increased from stage I to stage IV, suggesting that the SUA level reflected the severity of CRC and may help to evaluate the therapy effect as well as the prognoses of CRC patients [14]. In addition, an elevated serum level of uric acid was shown to be a significant prognostic marker for lymphatic metastasis in patients with colon cancer [23].…”
Section: Uric Acid As a Risk Factor In Various Cancersmentioning
confidence: 99%
“…In addition, serum uric acid in very high concentrations may trigger inflammatory stress, and it may also have intracellular pro-oxidative activity 4 , 13 . It is well-known that a pro-oxidant environment confers a growth advantage to tumor cells, and also influences carcinogenic potential by stimulating specific signaling cascades that regulate cell growth and apoptosis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Guo et al. developed an offline SPE‐UPLC–MS/MS method for the quantification of 8‐OHdG in urine samples and it was successfully applied to compare the urinary levels in patients with colorectal cancer with those of healthy controls, both in 2016 [103] and in 2018 [104]. Recently, the same research group developed an analytical method for the measurement of 8‐OHG in human urine, and again, this method was successfully applied for the determination of the RNA OS biomarker in the urine of both patients with colorectal cancer and healthy volunteers [105].…”
Section: Strategies To Quantify Biomarkers In Human Urine (2015–2020)mentioning
confidence: 99%